Targeting tumor–stromal interactions in bone metastasis - Esposito, Mark; Kang, Yibin (Pharmacology & therapeutics (Oxford), 2014)
Bone metastasis is a frequent occurrence in late stage solid tumors, including breast cancers, prostate or lung. However, the causes for this proclivity have only recently been elucidated. Significant progress has been made in the past decade toward understanding the molecular underpinnings of bone metastasis, and much of this research reveals a crucial role of the host stroma in each step of the metastatic cascade. Tumor-stromal interactions are crucial in engineering a pre-metastatic niche, accommodating metastatic seeding, and establishing the vicious cycle of bone metastasis. Current treatments in bone metastasis focus on latter steps of the metastatic cascade, with most treatments targeting the process of bone remodeling; however, emerging research identifies many other candidates as promising targets. Host stromal cells including platelets and endothelial cells are important in the early steps of metastatic homing, attachment and extravasation while a variety of immune cells, parenchymal cells and mesenchymal cells of the bone marrow are important in the establishment of overt, immune-suppressed metastatic lesions. Many participants during these steps have been identified and functionally validated. Significant contributors include integrins, (αvβ3, α2β1, α4β1), TGFβ family members, bone resident proteins (BSP, OPG, SPARC, OPN), RANKL, and PTHrP. In this review, we will discuss the contribution of host stromal cells to pre-metastatic niche conditioning, seeding, dormancy, bone-remodeling, immune regulation, and chemotherapeutic shielding in bone metastasis. Research exploring these interactions between bone metastases and stromal cells has yielded many therapeutic targets, and we will discuss both the current and future therapeutic avenues in treating bone metastasis.